Recurrent giant intrahepatic biliary cystadenoma: Case report and review of Literature - Digvijoy Sharma; Gangadhar Rao Gondu; Venu Madhav Thamma; Surya Ramachandra Varma Gunturi; Kunduru Nava Kishore; Jagan Mohan Reddy; Nagari Bheerappa (Indian Journal of Medical and Paediatric Oncology)
Biliary cystadenoma is a very rare cystic neoplasm of the liver that usually occurs almost exclusively in middle-aged women. These are slowly progressive tumours and cannot be safely differentiated from cystadenocarcinomas on preoperative imaging and hence should always be considered for resection. Historically these cystic tumors have been treated by a variety of techniques including aspiration, fenestration, internal drainage, partial resection resulting in high rates of recurrence. In addition biliary cystadenoma is a premalignant lesion and only surgical excision can differentiate it from its malignant counterpart, biliary cystadenocarcinoma.